Naming and Family Trees as Inter-Generational Epic Narratives in Bette-Obudu Culture, Cross River State - Liwhu Betiang; Esther Frank Apejoye-Okezie (Genealogy)
This study articulates how naming and family trees can become epic texts upon which intended or unintended meanings, identities and narratives can be decoded, including mutations in families, as basic units of society. Many studies in African anthroponym have articulated names and naming from differing perspectives, but have tended to ignore the diachronic and synchronic significance of looking at family trees which are woven in time and space through naming. Within the framework of Darwinian Theory of Evolution, we used in-depth interviews with a purposive sample of respondents from the Bette people of the Obudu local government area, to enable us to build family trees which were subtextually analyzed for meaning and mutations through six generations. Our findings enabled us to develop deeper insights into how a longitudinal articulation of naming and family trees can enhance our understanding of the synchronic realities, increased cultural aliteracy, dislocation of homesteads due to occupational shifts, changing ideas of kinship, patriarchal attitudes towards women and challenge of new technologies like DNA testing and new media within the Bette traditional kinship tradition. Significantly, naming and family trees, beyond dynastic delineations for identity, inclusivity and otherness, can become signifiers of a people’s epic progression and mutation, and, as it were, a tapestry of significant narratives of micro and macro family history.